Case report: Clinical workflow considerations for treating soft-tissue sarcoma on a 1.5-T MR-Linac - Gye Won Choi; Gary A. Eastwick; Leonard H. Kim (Technical Innovations & Patient Support in Radiation Oncology)
We present specific issues that arose when using a 1.5-Tesla MR-Linac to treat a series of 4 soft-tissue sarcoma (STS) patients. These issues arose from the combination of typical STS attributes (long, off-axis target) and MR-Linac design-specific limitations on field size and patient positioning. Despite the availability of on-line plan adaptation, STS patients were more efficiently treated after workflow changes to improve patient selection and immobilization. Other issues arising from off-axis STS target locations: geometric distortion of MR images and patient-specific QA, are discussed.